Association between active/passive Involution and lying flat among college students: the mediation role of perceived stress and anxiety - Lei Yang; Yunbing Zhang; Dongjun Zhang; Lujun Shen; Hui Feng (BMC Public Health)
Abstract Background In recent years, involution and lying flat have become popular in China. Involution is defined as the phenomenon in which people are actively or passively involved in irrational competition for limited social resources. Lying flat refers to the state in which people choose to give up their efforts and passively escape in the face of social pressure and continuous competition. Should involution lead to lying flat in college students? This study aimed to provide empirical support for examining the potential mechanism between active/passive involution and lying flat. Methods A cross-sectional survey of 1003 college students was conducted in Henan Province, China. Participants completed the Involution Behavior Scale, Perceived Stress Scale, Generalized Anxiety Disorder-7 Scale and Lying Flat Tendency Scale through Sojump platform. Correlation and mediation models were tested using SPSS 24.0 and PROCESS macro. Results The association between passive involution and lying flat was not only mediated through perceived stress and anxiety separately but also sequentially mediated through perceived stress and anxiety (Passive involution→ Perceived stress→ Lying flat: effect size = 0.075, 95% CI [0.042,0.113]; Passive involution→ Anxiety→ lying flat: effect size = 0.014, 95% CI [0.000, 0.031]; Passive involution→ Perceived stress→ Anxiety→ lying flat: effect size = 0.019, 95% CI [0.000, 0.039]). Active involution not only directly predicts lying flat but also indirectly predicts it through perceived stress (direct effect size = -0.301, 95% CI [-0.359, -0.242]; indirect effect size = -0.035, 95% CI [-0.055, -0.017]). Conclusions The results reveal the influence of active/passive involution on college students’ lying flat and the mediating role of perceived stress and anxiety. The findings can provide new insights into the relationship between involution and lying flat, as well as helping students better adapt to academic learning.